Շուշին արցախյան գոյապայքարում (1918–1920 թթ.) - Համլետ Հարությունյան (Հայկական ՍՍՀ գիտությունների ակադեմիա)
После приобретения независимости мусаватистское правительство Азербайджана поставило цель оккупировать неотделимую часть исторической Армении–Нагорный Карабах, Зангезур и Нахичеван. Арцахские армяне встали на борьбу против злостного врага ради свободы и независимости своей родины. Оплотом этой борьбы стал город-крепость Шуши. After the acquisition of independence, the Musavat government of Azerbaijan intended to conquer the indivisible part of historical Armenia – Nagorno-Karabakh, Zangezur and Nakhijevan. The Armenians of Artsakh rebelled against the mean enemy and fought for the independence of their native country. The fulcrum of that struggle was the fortress of Shushi.
Keywords: History; Political Science; Modern History; D History; J Political Science